THE INFLUENCE OF THE QUALITY OF GOOD CORPORATE GOVERNANCE (GCG) IMPLEMENTATION ON FINANCIAL PERFORMANCE IN ISLAMIC COMMERCIAL BANKS IN INDONESIA - Siti Maesaroh; Sri Wahyuni Asnaini; Fatrilia Rasyi Radita (Journal Of Communication Education, 2022)
ABSTRACTCorporate governance arises from the business need for good governance, which upholds the principles of transparency, trustworthiness, responsibility and fairness. Good Corporate Governance is corporate governance which is assessed as one of the public's assessments in deciding to invest in a corporate institution. The indicator to assess the quality of the implementation of Good Corporate Governance is seen from the Self-Assessment of each company which is taken from 11 criteria that apply as a whole.The purpose of this study was to analyze the determinants the effect of the implementation of Good Corporate Governance (GCG) on financial performance as measured by Return on Assets (ROA) and Non-Performing Financing (NPF) at Islamic Commercial Banks in Indonesia. The population is all Islamic Commercial Banks that have implemented GCG in accordance with Bank Indonesia regulations. This research is associative to see the relationship between one variable and another. The data used is secondary data from annual reports and corporate governance reports issued by each Islamic Commercial Bank for the 2016-2020 periods. The sample collected is 8 Islamic commercial banks with a total of N = 40. The results show that the implementation of GCG based on the data collected has an average of 1:55 to 2:20 which is included in the "Good" category. This means that the quality of GCG implementation is in accordance with the BUS 11 indicators set by Bank Indonesia.Keywords: Good Corporate Governance, financial performance, operational efficiencyABSTRAKTata kelola perusahaan muncul dari kebutuhan bisnis akan tata kelola yang baik, yang menjunjung tinggi prinsip-prinsip transparansi, kepercayaan, tanggung jawab dan keadilan. Good Corporate Governance adalah tata kelola perusahaan yang dinilai sebagai salah satu penilaian masyarakat dalam memutuskan untuk berinvestasi pada suatu institusi perusahaan. Indikator untuk menilai kualitas penerapan Good Corporate Governance dilihat dari penilaian masing-masing perusahaan yang diambil dari 11 kriteria yang berlaku secara keseluruhan.Tujuan penelitian ini adalah untuk menganalisis determinan pengaruh penerapan Good Corporate Governance (GCG) terhadap kinerja keuangan yang diukur dengan Return on Assets (ROA) dan Non Performing Financing (NPF) pada Bank Umum Syariah di Indonesia. Populasinya adalah seluruh Bank Umum Syariah yang telah menerapkan GCG sesuai ketentuan Bank Indonesia. Penelitian ini bersifat asosiatif untuk melihat hubungan antara satu variabel dengan variabel lainnya. Data yang digunakan adalah data sekunder berupa laporan tahunan dan laporan tata kelola perusahaan yang diterbitkan oleh masing-masing Bank Umum Syariah periode 2016-2020. Sampel yang dikumpulkan adalah 8 bank umum syariah dengan total N = 40. Hasil penelitian menunjukkan bahwa penerapan GCG berdasarkan data yang dikumpulkan memiliki rata-rata 1:55 hingga 2:20 yang termasuk dalam kategori “Baik”. Artinya, kualitas penerapan GCG sudah sesuai dengan indikator BUS 11 yang ditetapkan Bank Indonesia.Kata kunci: Good Corporate Governance, kinerja keuangan, efisiensi operasional